Inactivation of influenza virus as representative of enveloped RNA viruses on photocatalytically active nanoparticle and nanotubular TiO2 surfaces - Baudys, M; Sopha, Hanna Ingrid; Hodek, J; Rusek, J; Bartkova, H; Ulrychova, L; Macák, Jan; Weber, J; Krysa, J (Elsevier Science BV, 2024)
The recent pandemic showed us that there is a strong demand for standardized methods to evaluate the antiviral activity of different materials using enveloped RNA viruses (e.g. SARS-CoV-2, influenza virus). Virucidal activity can be achieved as a result of photoexcitation of a TiO2 photocatalyst under UV illumination. All standardized methods evaluating the virucidal activity of photocatalytic surfaces use bacteriophage Q -beta, a representative of small non -enveloped viruses. This work was thus devoted to the evaluation of the virucidal efficiency of photocatalytically active nanostructured TiO2 surfaces (nanotubular and nanoparticle) to inactivate the influenza virus with particular interest paid to the methodology of virucidal testing and the influence of the surface nanostructure (porosity). Two different TiO2 nanostructures were used in this study, namely nanoparticle and nanotubular structures. A significant decrease in the amount of viral RNA and titre was obtained after rinsing, because the virus was retained on the surface of the nanostructured TiO2 during exposure in the dark. The decrease can be understood as an additional effect of the surface porosity on the TiO2 virucidal activity after UV illumination. However, this fact was taken into account in the calculation of virucidal activity due to UV light. Both nanostructured TiO2 coatings have comparable porosity and thickness, but the photocatalytic activity (to oxidatively degrade aqueous pollutants) is higher for the nanoparticle than for the nanotubular surface. On the other hand, the virucidal activity is much higher for the nanotubular surface. This can be explained by the uniform and open structure of nanotubes resulting in a lower amount of virus being retained on the surface under dark conditions and the high surface area of the nanotubes.
Inaktivace chřipkového viru jako zástupce obalených RNA virů na fotokatalyticky aktivních nanočásticích a nanotubulárních površích TiO2
Keywords: Photocatalysis; Nanotubular layer; Porosity; Virucidal; Influenza virus; TiO2; Ti02; fotokatalýza; Nanotubulární vrstva; pórovitost; virucidita; Virus chřipky